PENERAPAN GOOD GOVERNANCE DALAM PENGELOLAAN DANA DESA STUDI KASUS PADA KABUPATEN KAMPAR - Maulina Agustiningsih (PEKBIS, 2020)
This study aims to obtain empirical evidence regarding the effect of the applicationof good governance in the management of village funds in Kampar Regency. Thepopulation in this study used all villages in Kampar District with 242 villages. Thesampling was done through purposive sampling technique with a total sample of 34villages in Kampar Regency. Data was collected through a questionnaire withresearch subjects being the headman, village secretary, financial officer and sectionhead. The analytical method contained in this research is Partial Leats Square (PLS)through the WarpPLS 6.0 application. The hypothesis obtained from the test resultsshows that the application of good governance influences the management of villagefunds. Based on the results of the study it can be concluded that by implementinggood governance in the management of village funds will be able to realize goodvillage fund management through transparency, accountability and participation fromthe community.